IMPLEMENTATION AND DATA VISUALIZATION OF 5G TESTBED USING OPEN-SOURCE SOFTWARE - Gabriel Limbong, Trizzos
The rapid development of technology in this day and age cannot be separated from internet connectivity. Internet connectivity continues to develop to meet human needs. One of the developments is fifth generation (5G) cellular network technology, which has a number of features and capabilities that can speed up and improve various aspects of modern technology. This technology has not yet spread evenly so it can be implemented through a testbed to understand how it works and its functionality. Implementation is carried out to understand 5G technology including testing network connectivity, protocol suitability, and functionality analysis. In this project, a 5G testbed with open-source components was implemented, a method of testing 5G connectivity using a publicly accessible core network project. The open-source 5G component that can be used is a combination of Open5GS and UERANSIM. Implementing a 5G testbed using Open5GS and UERANSIM allows users to test and understand 5G network connectivity comprehensively and at minimal cost. Apart from implementation, the 5G testbed can also be visualized to make it more representative, interactive and easy to analyze. This data visualization uses open-source software such as Prometheus, Node Exporter, and Grafana. The visualized parameters can help understand the 5G network and make monitoring easier if a larger network escalation is carried out later. There are technical challenges and a need for certain skills to develop a 5G testbed and visualize its data. However, the benefits are enormous including cost savings, easier flexibility, and the potential for discovery and innovation in 5G technology.